2019
DOI: 10.1080/09687599.2019.1647148
|View full text |Cite
|
Sign up to set email alerts
|

Gender, sexuality and relationships for young Australian women with intellectual disability

Abstract: Gender has often been overlooked in the lives of people with intellectual disability, resulting in a limited understanding and service response. This is in part due to a lack of knowledge about the way people with intellectual disability negotiate and build a gendered identity. In this article we present research undertaken with six young women with an intellectual disability who worked with the first researcher to co-develop some stories from their lives. We show how, facilitated by an innovative method which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 56 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…Seven articles collected information on the desires and expectations that people with ID have about affective and intimate relationships [ 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. These studies were all qualitative and included males and females between 16 and 60 years old.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven articles collected information on the desires and expectations that people with ID have about affective and intimate relationships [ 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. These studies were all qualitative and included males and females between 16 and 60 years old.…”
Section: Resultsmentioning
confidence: 99%
“…Romantic relationships were highly significant to women as they functioned as a productive nexus for understanding gender in their lives. Developing their roles—or aspirations—as “girlfriend”, “fiancée”, “bride”, and “wife” positioned the women as desirable, capable, and lovable [ 43 ]. Having a partner suggested a sense of normality and being an ordinary member of society [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…In our study we explored gender identity among disabled people and found that disabled people who identify as transgender were more likely to identify developmental disabilities as the main disability compared to disabled cisgender people. This is important because historically, gender identities were not viewed as identities disabled people were capable of claiming [ 112 , 113 ], and transgender people were pathologized as morally corrupt and ethically disabled [ 114 , 115 ]. Additionally, due to this stigmatization, transgender people have, at times, resisted disability identities [ 116 ].…”
Section: Discussionmentioning
confidence: 99%
“…This mirrors in its part the gendered nature of the issue: men tend to be seen more sexual than women and are thus likely to be granted more opportunities to express their sexuality than women. This imbalance is also represented in research literature on sexuality and intellectual disability, where there is little research on how women with intellectual disability experience their sexual lives (McCarthy, 1999(McCarthy, , 2002(McCarthy, , 2014O'Shea & Frawley, 2020).…”
Section: What Is Sex? What Is Fair?mentioning
confidence: 99%
“…When it comes to intellectual disability and sexuality, at least in any affirmative sense, the default position seems to be male: men with intellectual disability are seen as agents who legitimately may seek intimacy and sexual pleasure. But for women with intellectual disability, the reality is somewhat different: they are seen as sexually naïve, more vulnerable to sexual abuse than men and consequently in need of more protection (O'Shea & Frawley, 2020;Young, Gore, & McCarthy, 2012). This seems like a reasonable reaction to the fact that women with intellectual disability are indeed more likely to experience sexual abuse than men (e.g.…”
Section: What Is Sex? What Is Fair?mentioning
confidence: 99%